Inayat ullah As A Novelist-An Analytical Study - Zainud Din Akhtar; Dr Ahsan-ul-Haq (Zaban-o-Adab, 2022)
Urdu literature has been lucky to have got high ranking writers in other departments besides in itself. Military profession is at the top of them.The list of these intellectual is long including Shafiq ur Rehman, Abdul Majeed Adam, Faiz Ahmad Faiz, Chiragh Hassan Hasrat, Syed Zamir Jafry. If another name is added in this list definitely it will be the name of Inayatullah. His litrary and militarily contributions go side by side. He was including in that very initial squad of Pakistan Air Force which saluted the founder of Pakistan at Peshawar. He was a great Novelist, Journalist and Narrator of Incidents. He wrote more than one hundred books. Besides Historical and social novels he wrote on topics like Reward and punishment detection and hunting Irony humor psychology which clearly display his per faction of art.He wrote with pen name like Meem Alif, Altamash, Ahmad Yar Khan, Sabir Husain Rajpoot, Waqas, Ibne Sehra and Inayatullah.